Pogonophryne neyelovi, a new species of Antarctic short-barbeled plunderfish (Perciformes, Notothenioidei, Artedidraconidae) from the deep Ross Sea - Eakin, Richard R. (Plazi.org taxonomic treatments database, 2013)
This dataset contains the digitized treatments in Plazi based on the original journal article Shandikov, Gennadiy A., Eakin, Richard R. (2013): Pogonophryne neyelovi, a new species of Antarctic short-barbeled plunderfish (Perciformes, Notothenioidei, Artedidraconidae) from the deep Ross Sea. ZooKeys 296: 59-77, DOI: http://dx.doi.org/10.3897/zookeys.296.4295, URL: http://dx.doi.org/10.3897/zookeys.296.4295